Role Optimization and Strategic Adjustment of Procuratorial Organs in Promoting Corporate Compliance Construction from the Perspective of Environmental Pollution Crimes - Zhu, Junqi (Transactions on Economics, Business and Management Research, 2024)
With the improvement of environmental protection awareness and the in-depth rule of law, the compliance construction of environment-related enterprises has become the focus of social attention. It is necessary to discuss the role of optimization and strategy adjustment of the procuratorial organs in promoting the construction of corporate compliance from the perspective of environmental pollution crimes. Corporate compliance and the current situation of enterprises involved in environmental pollution crimes in China deserve attention. Meanwhile, the procuratorial organs play the role of supervisor in the regulation to promote the compliance of enterprises with environmental pollution, but its supervision effect is limited. The procuratorial organs with a supervisory role when promoting corporate compliance aim to enhance corporate development. During the enterprise compliance, whether an enterprise complies or not needs to be analyzed from the perspective of game theory, which is always driven by its interests and external regulatory incentives. Compliance construction and improvement of legal procedures from the perspective of norms should consider incentives and regulations for the implementation of compliance plans, the construction of the legal status of third-party organizations, and post-event incentives and feedback from third-party organizations.